2016
DOI: 10.1016/j.rmr.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation non invasive. Les conseils 2015 du Groupe assistance ventilatoire (GAV) de la Société de pneumologie de langue française (SPLF)

Abstract: A task force issued from the Groupe Assistance Ventilatoire (GAV) of the Société de Pneumologie de Langue Française (SPLF) was committed to develop a series of expert advice concerning various practical topics related to long-term non invasive ventilation by applying the Choosing Wisely methodology. Three topics were selected: monitoring of noninvasive ventilation, the interpretation of data obtained from built-in devices coupled to home ventilators and the role of hybrid modes (target volume with variable pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…In obstructive lung diseases, short rise times (≤150 ms) favor a shorter inspiratory time (TI) and a favorable I:E ratio (e.g., ≈ 1:3). Conversely, rise times of 150–250 ms are commonly used in restrictive lung diseases [4, 14, 24]. Longer rise times may impinge on pressurization time and affect efficacy of ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…In obstructive lung diseases, short rise times (≤150 ms) favor a shorter inspiratory time (TI) and a favorable I:E ratio (e.g., ≈ 1:3). Conversely, rise times of 150–250 ms are commonly used in restrictive lung diseases [4, 14, 24]. Longer rise times may impinge on pressurization time and affect efficacy of ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Además, se debe tener en cuenta que todos los tipos de ventiladores son diferentes y, en consecuencia, es muy difícil, si no imposible, conocer todos los algoritmos que operan, lo que puede generar dificultades o incluso errores. También hay que saber que cada fabricante determina en sus ventiladores diferentes parámetros o settings y de ahí la necesidad de conocer y entender los equipos para mejorar su aplicación clínica [65][66][67][68] .…”
Section: Ventilación Mecánicaunclassified
“…Thus, the best compromise between patient comfort and efficacy must be sought for. Pattern of use (fragmentation vs. continuous use) can be an indicator of discomfort and side-effects (leaks, pain or discomfort related to interface), co-morbidities (nycturia, use of diuretics) or symptomatic patient-ventilator asynchrony ( Figure 1 ) ( 7 , 45 , 46 ). Evolution of total time spent under NIV and changes in pattern of use may be indicative of an exacerbation with a risk of hospital admission ( 47 ).…”
Section: Introductionmentioning
confidence: 99%
“…Arbitrary threshold values for acceptable leaks are commonly reported by several manufacturers: the threshold of 24 L/min often referred to was first mentioned in a study by Teschler et al ( 53 ): the relevance of this value is questionable today since the efficacy of ventilator turbines and their capacity to compensate for leaks has improved substantially. A statement by the French GAV-O 2 group suggested that leaks are considered troublesome essentially 1/ if they impact on patient comfort and compliance and 2/ if they cause recurrent nocturnal desaturations and episodes of hypercapnia ( 46 ).…”
Section: Introductionmentioning
confidence: 99%